Optimization Simulation Research on Middle-Deep Geothermal Recharge Wells Based on Optimal Recharge Efficiency - Deng, Song; Ling, Dingkun; Zhao, Huijun; Shen, Xin; Du, Huajun; Liu, Lu (Frontiers in Energy Research, 2020)
In order to solve the low recharge efficiency of middle and deep geothermal Wells, a thermo-hydro-mechanical (THM) model integrating geothermal production and reinjection was established, and the relationship model between recharge efficiency and production well temperature was built to obtain the optimal recharge efficiency. In view of the different well spacing between reinjection and production wells, the different well spacing between production wells and different reinjection well types, numerical simulation and comparative analysis were carried out under the optimal recharge efficiency. The results show that under the optimal recharge efficiency, the change in well spacing has the greatest impact on the exploitation of production wells. The well spacing of production wells is gradually reduced from 600 m to 20 m, and the time of thermal breakthrough in production wells is getting earlier and earlier. However, when the spacing between the production wells reach 200 m, thermal breakthrough hardly occurs. Compared with different well spacings, different reinjection well types have less impact on the exploitation of production wells, and the situation of production wells under one reinjection and two production is better than one reinjection and one production. Therefore, it is proposed that under the optimal recharge efficiency of 40.41–72.52%, the most suitable approach is to use one reinjection and two production as this well spacing between the reinjection and production well above 400 m, the well spacing between the production wells above 200 m and the reinjection wells of horizontal wells are optimal and most suitable for geothermal exploitation.